2019
DOI: 10.3390/genes10110938
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Runs of Homozygosity, Effective Population Size, and Detection of Positive Selection Signatures in Six Chinese Goat Breeds

Abstract: Detection of selection footprints provides insight into the evolution process and the underlying mechanisms controlling the phenotypic diversity of traits that have been exposed to selection. Selection focused on certain characters, mapping certain genomic regions often shows a loss of genetic diversity with an increased level of homozygosity. Therefore, the runs of homozygosity (ROHs), homozygosity by descent (HBD), and effective population size (Ne) are effective tools for exploring the genetic diversity, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 55 publications
10
46
0
Order By: Relevance
“…Long runs of homozygosity have been observed to be persistent in inbred individuals, suggestive of unusually low mutation rates, high linkage disequilibrium (LD), and low recombination rates at certain genomic regions [ 9 ]. ROH accumulation in certain genomic positions has been used to analyze the demographic history in humans [ 10 , 11 ] and livestock populations [ 12 , 13 ]. A study also used ROH to compare and characterize beef and dairy cattle breeds [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long runs of homozygosity have been observed to be persistent in inbred individuals, suggestive of unusually low mutation rates, high linkage disequilibrium (LD), and low recombination rates at certain genomic regions [ 9 ]. ROH accumulation in certain genomic positions has been used to analyze the demographic history in humans [ 10 , 11 ] and livestock populations [ 12 , 13 ]. A study also used ROH to compare and characterize beef and dairy cattle breeds [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long segments were abundant in the North West population. [25] recent study revealed a high mean ROH in the long length category (>30 Mb), and their study suggested that inbreeding is more recent and is indicative of demographic decline. This is possible considering the extensive management systems of goats in the region, where goats are on free-range or are herded with other ocks for some part of the year, although some researchers have argued that such extensive systems may lead to inbreeding [58,22].…”
Section: Discussionmentioning
confidence: 97%
“…The inbreeding coefficient based on ROH (F ROH ) was estimated as the proportion of genome in ROH over the overall length of the genome covered by the involved SNPs using detectRUNS packages in R software [ 19 ]. The following parameters were set to define the ROHs: (i) a minimum length of ROH was set to 1 Mb, (ii) the maximum distance between two consecutive SNPs was allowed to 1 Mb, (iii) one possible heterozygote and one missing genotype were allowed for each ROH, and (iv) to minimize the number of ROH that could occur by chance, the minimum number of SNPs that constituted an ROH was calculated by the formula proposed by Lencz, Lambert [ 20 ]: where α is the false positive ROH in percentage (set to 0.05 in this study), n s is the number of SNPs per individual, n i is the number of individuals tested, and het is the proportion of heterozygosity across all SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…The JGM goats presented the highest values and ACM displayed the lowest value for both H O (JGM = 0.401 ± 0.20, ACM = 0.367 ± 0. 19) and H E (JGM = 0.391 ± 0.20, ACM = 0.384 ± 0.20). The ACM exhibited the highest average values for both inbreeding coefficient estimators (F ROH = 0.086, F HOM = 0.074) whereas the ZWM showed the lowest F ROH (0.017).…”
Section: Genetic Diversity Within Breedsmentioning
confidence: 98%